Global Supply Chain Restructuring: Business Strategy Amid Geopolitical Fragmentation - Dina Nurul Fathiya (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
Global geopolitical fragmentation has triggered significant changes in the structure of international supply chains. The COVID-19 pandemic, trade wars, and tensions between economic blocs have exposed the vulnerability of single sourcing and highly concentrated supply chain models. This condition requires companies to review their business strategies to be more adaptive, resilient, and sustainable. This study aims to map geopolitical risks and supplier concentrations, evaluate the impact of friend-shoring and near-shoring strategies on costs and resilience, and test the effectiveness of site portfolio designs and supplier contracts in improving supply chain resilience with cost efficiency. The research method uses a qualitative approach with comparative case studies combined with descriptive quantitative analysis. Data was collected through questionnaires, in-depth interviews with supply chain managers, analysis of company documents, as well as SEM-PLS modeling to test the relationship between restructuring strategies, geopolitical risk, and company performance. The results show that dual/triple sourcing and hybrid sourcing strategies are more effective in increasing resilience with relatively controlled cost increases. The implementation of digital technologies such as ERP, predictive analytics, and digital twins has been proven to strengthen scenario planning capabilities and reduce distribution delays. The findings also confirm the trade-off between cost, resilience, and sustainability, where companies that are able to balance these three aspects gain a long-term competitive advantage. The implications of this study confirm the need for a geo-risk-adjusted total cost framework as the basis for the formulation of a global supply chain restructuring strategy. Companies are encouraged to adopt a digital and sustainability-oriented approach to be better prepared for geopolitical uncertainty.